Mathematical methods of the theory of elasticity - Volume 2 - Parton, Vladimir Zalmanovič (Mir Publishers, 1984)
Sadržaj: 4. The method of separation of variables in the problems of the theory of elasticity ; 5. Application of analytical functions in plane problems ; 6. Integral representation and integral transformations ; 7. The methods of potential in the theory of elasticity ; 8. Variational and difference methods in the theory of elasticity